Eksplorasi Kesiapan Perguruan Tinggi Mendukung Pengembangan UMKM Halal Food - Nenengsih (El-kahfi | Jurnal Ekonomi Islam, 2023)
This research aims to analyze the readiness of universities in West Sumatra to support the development of halal food SMEs. Halal food SMEs have great potential for growth and development, especially in countries with a majority Muslim population like Indonesia. However, there are various challenges faced by halal SMEs, such as low understanding of halal certification and limited socialization activities. Therefore, universities, as educational and research institutions, play a strategic role in assisting the development of halal food. This study adopts a descriptive analysis approach by collecting data through literature review and interviews with the academic community of universities in West Sumatra. The results show that universities in the region have limited involvement in supporting the halal industry. Although some universities have established study centers or halal centers, direct participation is still relatively low. The role of universities in the development of halal food SMEs can be carried out through various activities, such as producing high-quality human resources, establishing halal product research centers, conducting socialization, education, mentoring, and consultation related to halal certification, as well as developing halal literacy. Halal science and technology research are also crucial in producing halal products that meet consumer expectations. To address global challenges and enhance the competitiveness of halal food SMEs, universities need to enhance their readiness by intensifying their roles and collaborations among universities, government agencies, business entities, and other relevant institutions. By doing so, the development of halal food SMEs in West Sumatra can be effectively implemented, contributing to the regional economy, and meeting the increasing needs of Muslim consumers.